KOMPETENSI LITERASI DIGITAL GURU: PENDEKATAN LITERATURE REVIEW - Saputra, Yudha Nata (Universitas Wiralodra, 2026)
In this digital era, teachers are required to not only master the subject matter, but also be able to utilize technology to improve the quality of learning. Teachers' digital literacy competence is the key to success in creating effective and relevant learning in the digital era. By continuing to develop digital literacy competencies, teachers can not only provide better learning experiences for students but also prepare them for the future. It is important for teachers to have digital literacy competencies, so it is necessary to conduct a search related to the state of digital competencies owned by teachers including efforts that have been made in order to improve teacher digital competencies. The method used in this research is systematic literature review. The results of the literature search can be concluded that the digital literacy competence of teachers is quite good, seen from the variety of teaching aids and digital reading materials including the use of digital books. Learning activities that are already based on technology and information as well as the use of technology in the school environment and the application of digital technology in school services. Teachers' digital literacy competencies are quite good, also seen from indicators of information and data literacy, communication and collaboration, digital content creation, digital security and problem solving. Then the various efforts made to improve teachers' digital literacy competencies are effective.